The Music Homophony in Kurdish Composed Songs - Sarmand Fuad Mohammed; Muhammad Azeez zaza; Dlawer Mustafa Muhammad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
It is a qualitative study, based on descriptive and analytical method. The homophonic process is discussed to work on matching the melody in the construction of Kurdish songs in southern Kurdistan. The process includes two elements, melody and musical accompaniment. In this study, a musical analysis is conducted for the units and components of the research sample, and then the results are presented. During this study many models of previously popular usage methods are discussed, besides revealing many new techniques to enrich this process in Kurdish music, as recommendations by the researchers to stakeholders.